2014
DOI: 10.1111/bjh.13102
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of early death in a cohort of 162 adult haemophagocytic syndrome: impact of triggering disease and early treatment with etoposide

Abstract: Reactive haemophagocytic syndrome is a life-threatening disease for which factors influencing the outcome remain unclear. We sought to identify determinants of early mortality in patients with reactive haemophagocytic syndrome by conducting a non-interventional retrospective multicentre study in three tertiary care teaching hospitals over a 6-year period. The medical files of 162 patients fulfilling our diagnostic criteria of haemophagocytic syndrome were reviewed. Patients were classified according to 30-d ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
150
1
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(179 citation statements)
references
References 25 publications
17
150
1
7
Order By: Relevance
“…Case series of adults treated with a variety of regimens report a 30-day mortality of 20% to 44% and overall mortality of 50% to 75%. [25][26][27]31,74,75 Patients with HLH associated with malignancy suffer a worse prognosis.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…Case series of adults treated with a variety of regimens report a 30-day mortality of 20% to 44% and overall mortality of 50% to 75%. [25][26][27]31,74,75 Patients with HLH associated with malignancy suffer a worse prognosis.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…In refractory cases, immunosuppressive agents such as steroids and calcineurin inhibitors (CI) and etoposide are used according to the HLH-2004 protocol. Despite this treatment, the mortality is reportedly high at 20-75% (7)(8)(9). Several previous studies showed that the following clinical and laboratory findings were risk factors associated with a very poor prognosis: underlying malignant lymphoma, increasing age, a low platelet count, management without etoposide (8), low levels of albumin (9) and low levels of fibrinogen (10).…”
Section: Introductionmentioning
confidence: 99%
“…Age .60 years was found to have a poorer overall prognosis. 81 One study found that male sex lead to poorer outcomes, although this has not …”
Section: Prognosismentioning
confidence: 99%
“…81, The treatment of HLH should be aimed at suppressing the immune system and treating the underlying disorder. The first international treatment protocol for HLH included an 8-week induction therapy with etoposide, high-dose dexamethasone, and intrathecal methotrexate for patients with central nervous system involvement followed by maintenance with cyclosporine; however, this regimen is used mainly in FHL.…”
Section: Treatmentmentioning
confidence: 99%